From Christ to Confucius: German Missionaries, Chinese Christians, and the globalization of Christianity 1860-1950 - Wu, Albert (Yale University Press, 2016)
Introduction: Perceptions of failure -- The missionary impulse -- Responding to failure -- Missionary optimism -- A fractured landscape -- Order out of chaos -- Falling in love with Confucius -- Unfulfilled promises -- Fruits of the spirit -- Conclusion: Failure and success